Art direction - Mahon, Nik (Basics advertising, 2010)
A guide to the role of the art director. It examines the techniques, approaches and secrets involved in the development of creative advertising concepts. It emphasizes the importance of seeing things differently, and providing the audience with something to discover. It examines the process of visualizing and exploring different ideas.